Animalia dubia vel fabulosa jako przyczynek do polemiki antyheretyckiej w Komentarzu do Księgi Izajasza (VI 13, 19 - 14, 1) św. Hieronima - Krzyszczuk, Łukasz (Vox Patrum, 2018)
The article presents the way of using paradoxographical information regarding the matter of animals with doubtful identification in leading anti-heretical and Anti-Judaist polemic on the example of the sixth book Commentary on Isaiah by Jerome of Stridon. In the allegoric explanation of Is 13:19 - 14:1 Bethlehem monk juxtaposed widely known information about mythological creatures with the well-known story from the Book of Genesis about the conflict of Esau with Jacob. This let him explain why the followers of Judaism and heretics are the allies when it comes to fighting with the Church. Anti-Judaism and anti-heretic polemic was one of the most important topic brought up by alexandrine exegesis that Jerome was influenced by during his whole life.